Perlakuan Akuntansi Pembiayaan Gadai Emas (Rahn) Berdasarkan PSAK 107 di PT. Pegadaian Syariah ( Studi Kasus di PT. Pegadaian Syariah Jombang) - Rifa Tussalam; Meta Ardiana (JFAS : Journal of Finance and Accounting Studies, 2020)
The growth of Islamic financial institutions in Indonesia is very rapid, this is marked by the emergence of many Islamic financial institutions. Like sharia banks and sharia pawnshops the emergence of sharia pawnshops, the public interest increases, this happens because it does not stipulate usury and in accordance with Al-Quan and Hadist. Sharia pawnshops have several products, which are highly sought after by customers, namely rahn, because customers can guarantee valuables such as gold, BPKB, electronic goods and other valuables, but the products that are highly sought after by customers, namely gold. The purpose of the research was to find out the treatment of accounting for gold pawning financing based on PSAK 107 in the Jombang sharia pawnshop using descriptive qualitative research. The results of the study are the significance of Jombang sharia pawnshops using psak 107 for financing gold pawns